Hepatitis B and C Seroprevalance in Frontier Corp Recruits at Pre-employment Screening - Abrar, Syed Mohammad; Shah, Syed Sajid Ali; Rahim, Sheema (Infectious Diseases Journal of Pakistan, 2023)
Backgopurnd: Pakistan carries a high burdens of chronic hepatitis and mortality due to hepatic failure and hepatocellular carcinomas. Keeping in view this potential threat all the Frontier Corps recruits are screened for the Hepatitis B surface antigen (HBsAg) and Hepatitis C virus antibodies (Anti-HCV) before induction. Subjects and Methods: Sera of healthy adult individuals who presented for medical evaluation as pre-recruitment criteria in the Thall Scouts, Frontier Corps (FC), Khyber Pukhtunkhwa (KPK) were screened for HBsAg and Anti-HCV by rapid method. Positive cases were confirmed by Enzyme-linked immunosorbent assay (ELISA) technique from Combined Military Hospital (CMH), Peshawar. Results: A total of 552 individuals were examined. Out of these, 12 (2.17%) individuals were HBsAg positive whereas 7 (1.26%) were positive for anti-HCV. None of the recruits was positive for both HBsAg and Anti-HCV. Conclusion: This study which evaluated predominantly healthy young male population at KPK, showed a high seroprevalence of HBsAg and Anti-HCV. Hepatitis B vaccination is strongly recommended for our young populations. Key words: Hepatitis, prevalence, hepatocellular carcinoma, hepatitis B & C.